2014
DOI: 10.1111/jsm.12553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Botulinum-A Toxin Injection into Bulbospongiosus Muscle on Ejaculation Latency in Male Rats

Abstract: Introduction Premature ejaculation (PE) is the most common male sexual dysfunction. A variety of pharmacotherapeutic strategies have been employed to treat men suffering with lifelong PE. However, there are currently no pharmaceuticals approved by the U.S. Food and Drug Administration specifically designed for PE treatment. Aim Given that the bulbospongiosus muscle is involved in the ejaculatory reflex in both humans and rode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…He subsequently demonstrated that percutaneous injection of either 0.5 or 1 unit Botulinum toxin A into the bulbospongiosus muscle bilaterally significantly increased ejaculatory latency in male rats (0.5 unit: 314.6±193.1 to 507.6±277.8 s, P=0.021; 1 unit: 264.4±129.1 to 598.2±352.5 s, P=0.008) in a dose-dependent manner compared to pre-treatment latency without affecting their ability to achieve mounts, intromissions, or ejaculation (156). Mean ejaculation latency reached its peak 11 days after injection and decreased sharply 14 days after injection at both doses.…”
Section: New Therapeutic Targets and Emerging Drugsmentioning
confidence: 99%
“…He subsequently demonstrated that percutaneous injection of either 0.5 or 1 unit Botulinum toxin A into the bulbospongiosus muscle bilaterally significantly increased ejaculatory latency in male rats (0.5 unit: 314.6±193.1 to 507.6±277.8 s, P=0.021; 1 unit: 264.4±129.1 to 598.2±352.5 s, P=0.008) in a dose-dependent manner compared to pre-treatment latency without affecting their ability to achieve mounts, intromissions, or ejaculation (156). Mean ejaculation latency reached its peak 11 days after injection and decreased sharply 14 days after injection at both doses.…”
Section: New Therapeutic Targets and Emerging Drugsmentioning
confidence: 99%
“…Nevertheless, further studies in humans are essential to evaluate and corroborate a PE potential benefit of botulinum-A toxin injection in bulbospongiosus muscle [34].…”
Section: E Effect Of Botulinum-a Toxinmentioning
confidence: 99%
“…Despite the bilateral injection did not produce a significant impact on ejaculation latencies, rats treated with either 0.5 or 1 unit botulinum-A toxin exhibited significantly longer ejaculatory latencies compared with their pretreatment performance. According to the study, the ejaculation latency reached its peak 11 days after injection and decreased sharply 14 days after injection [34].…”
Section: E Effect Of Botulinum-a Toxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal model has shown that BoNT-A injection into the bulbospongiosus muscle is a safe and effective treatment that extends ejaculatory latency in rats without affecting the ability to engage in sexual activity or achieve ejaculation [76]. Currently, a Phase II trial is being conducted to examine the safety and efficacy of BoNT-A for the treatment of premature ejaculation [77] and at this stage, it is too early to adopt BoNT injection as a valid treatment for premature ejaculation.…”
Section: Premature Ejaculationmentioning
confidence: 99%